Ionic liquid functionalized hydrogen bond organic porous framework composite resin bead as well as preparation method and application thereof
Through the preparation method of ionic liquid functionalized hydrogen bonded organic porous frame composite resin beads, the existing resin has poor recovery and low selectivity in spent fuel post-treatment, the deep purification of radionuclides is achieved, the safe drinking water standards are met, and the mass transfer efficiency and purification performance are improved.
Patent Information
- Application Number
- CN202411893693.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-04-25
AI Technical Summary
Existing commercial resins have poor recovery and low selectivity in spent fuel post-treatment, and cannot deeply purify radionuclide pollutants. The powdered adsorbent has low mass transfer efficiency and poor mechanical strength in large pumping systems, and high transportation costs.
The preparation method of ionic liquid functionalized hydrogen-bonded organic porous frame composite resin beads is adopted. Through the synthesis of ionic liquid IL and hydrogen-bonded organic porous frame HOF, IL-HOF/PES composite resin beads are formed by combining polyethersulfone PES to achieve deep purification of radionuclides.
The concentration of ReO4- in nuclear wastewater has been purified to 0.049 ppb, meeting the safe drinking water standards of the World Health Organization and the US Environmental Protection Agency, and the deep purification performance is better than existing commercial resins and porous adsorbents. At the same time, the mass transfer efficiency in the adsorption column is improved, avoiding material leakage and secondary pollution.
Smart Images

Figure CN119869471A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of material preparation, and in particular to an ionic liquid functionalized hydrogen bond organic porous framework composite resin bead and a preparation method and application thereof. Background Art
[0002] Nuclear energy is an important clean energy source, and the development of nuclear power is one of the important ways to achieve energy supply and low carbon emissions. However, a large amount of radionuclides will be produced in the reprocessing of spent fuel. Water-soluble radionuclides with long half-life, high mobility and chemical toxicity pose a long-term threat to the entire biological system. The currently used commercial resins (such as Purolite A532E and A530E) have poor recyclability, low selectivity, and lack the ability to deeply purify radioactive wastewater. Although functional adsorption materials including metal organic frameworks, covalent organic frameworks, porous aromatic frameworks, etc. have been widely used in the adsorption research of radioactive pollutants, most of them are stopped at pilot-scale production due to the problems of low mass transfer efficiency, poor mechanical strength, difficult separation and recovery, and expensive transportation costs of powdered adsorbents in large-scale pumping systems.
[0003] Therefore, it is crucial to develop new resins with well-defined and designable structures, rich and orderly distributed functional groups, and to meet the needs of large-scale deep purification of wastewater in practical industrial applications. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing ionic liquid functionalized hydrogen bonded organic porous framework composite resin beads in order to solve the technical defects in the prior art.
[0005] Another object of the present invention is to provide an ionic liquid functionalized hydrogen bonded organic porous framework composite resin bead;
[0006] The invention also provides an application of ionic liquid functionalized hydrogen bond organic porous framework composite resin beads in the deep treatment of radioactive nuclides.
[0007] The technical solution adopted to achieve the purpose of the present invention is:
[0008] A method for preparing ionic liquid functionalized hydrogen bonded organic porous framework composite resin beads comprises the following steps:
[0009] Step 1, synthesizing an ionic liquid functionalized hydrogen-bonded organic porous framework IL-HOF using an ionic liquid IL and a hydrogen-bonded organic porous framework HOF, wherein the ionic liquid is copolymerized by the same or different monomers containing alkenyl groups, at least one of the monomers includes an imidazolium group, and at least one of the monomers includes an amino group or a hydroxyl group, and the amino group or the hydroxyl group reacts with a naked carboxyl group in the HOF by esterification or amide reaction;
[0010] Step 2, compounding the IL-HOF obtained in step 1 with PES to form an ionic liquid functionalized hydrogen bonded organic porous composite resin IL-HOF / PES dispersion;
[0011] Step 3, dropping the IL-HOF / PES dispersion obtained in step 2 into a pre-cooled water / ethanol solution to cause phase inversion, and then standing and drying to obtain composite resin beads IL-HOF / PES.
[0012] In the above technical solution, the ionic liquid IL is a copolymer of 1-vinyl-3-aminoimidazolium, a copolymer of 1-vinyl-3-hydroxyimidazolium, or a copolymer of bisvinylimidazolium and an olefin-containing alcohol or ammonia.
[0013] In the above technical solution, the particle size of the composite resin beads IL-HOF / PES is 2.00±0.1 mm.
[0014] In the above technical scheme, step 1 is specifically as follows: under a protective gas atmosphere, the hydrogen-bonded organic porous framework HOF and the ionic liquid IL are fully mixed, an initiator solution is injected to initiate polymerization, heating is performed, an equal amount of initiator solution is injected again, and the reaction is heated again to obtain a solid product. After cooling, the obtained solid product is washed, and the ionic liquid functionalized hydrogen-bonded organic porous framework IL-HOF is obtained after heating and drying.
[0015] In the above technical scheme, step 2 is specifically as follows: under heating conditions, PES is dissolved and fully stirred to obtain a transparent PES solution of uniform viscosity, and the ionic liquid functionalized hydrogen bond organic porous framework IL-HOF prepared in step 1 is added while hot, and continuous stirring is performed to allow PES and IL-HOF to form a uniform IL-HOF / PES dispersion.
[0016] In the above technical solution, the mass ratio of the hydrogen-bonded organic porous framework HOF, the ionic liquid IL and the initiator in step 1 is (0.8-1.5):(3.2-6.0):(0.4-0.6), and the initiator solution is a methanol solution of 2,2'-azobis(isobutyronitrile).
[0017] In the above technical scheme, the reaction temperature in step 1 is 65-80° C., the reaction time is 24-48 hours, and the washing solution is one of methanol or N,N-dimethylformamide.
[0018] In the above technical solution, the mass ratio of PES to IL-HOF in step 2 is 1.25:1, the reaction temperature is 60° C. to 80° C., and the reaction time is 24 to 48 hours.
[0019] Another aspect of the present invention also includes an ionic liquid functionalized hydrogen bond organic porous framework composite resin bead.
[0020] Another aspect of the present invention also includes the use of ionic liquid functionalized hydrogen bond organic porous framework composite resin beads in the deep treatment of radioactive nuclides.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] 1. The particle size of the ionic liquid functionalized hydrogen bond organic porous framework composite resin beads IL-HOF / PES of the present invention can reach the millimeter level, which can be expanded to the kilogram level for batch preparation. The exposed carboxyl groups in HOF are post-modified by the ionic liquid IL, and the cross-linking polymerization between HOF and the functionalized ionic liquid can be achieved through simple esterification or amide reaction. PES and the ionic liquid functionalized hydrogen bond organic porous framework IL-HOF are combined into microspheres, which can effectively prevent excessive agglomeration of crystalline powder, avoid the hidden dangers of material leakage and secondary pollution to water bodies, and help to improve the mass transfer efficiency in the adsorption column.
[0023] 2. The imidazolium in the ionic liquid IL used in the present invention reacts with ReO4 - The prepared ionic liquid functionalized hydrogen bond organic porous framework composite resin beads IL-HOF / PES can absorb ReO4 – The concentration was purified to 0.049 ppb, which for the first time simultaneously met the safe drinking water standards of the World Health Organization (WHO) and the US Environmental Protection Agency. Its deep purification performance is better than that of currently used commercial resins and reported porous adsorbents. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 Shown is a technical roadmap for preparing PG-HOF / PES using the preparation method of the present invention.
[0025] Figure 2 Shown is a schematic diagram of the reaction process of PG-HOF / PES prepared by the preparation method of the present invention.
[0026] Figure 3 (a), (b) and (c) show the X-ray diffraction patterns of HOF, PG-HOF, PG-HOF / PES; COF, PG-COF, PG-COF / PES; and MOF, PG-MOF, PG-MOF / PES prepared by the preparation method of the present invention, respectively.
[0027] Figure 4 (a), (b) and (c) show the Fourier transform infrared spectra of HOF, PG-HOF, PG-HOF / PES; COF, PG-COF, PG-COF / PES and MOF, PG-MOF, PG-MOF / PES prepared by the preparation method of the present invention, respectively.
[0028] Figure 5 The figure shows the adsorption removal rates of perrhenate by PG-HOF, PG-COF and PG-MOF, PG-HOF / PES, PG-HOF / PES, PG-COF / PES and PG-MOF / PES prepared by the preparation method of the present invention.
[0029] Figure 6 Shown are X-ray photoelectron spectra of HOF, PG-HOF and PG-HOF / PES prepared by the preparation method of the present invention.
[0030] Figure 7 Shown are the thermogravimetric curves of HOF, PG-HOF and PG-HOF / PES prepared by the preparation method of the present invention.
[0031] Figure 8 Shown are the high-resolution electron images and element distribution of the HOF prepared by the preparation method of the present invention.
[0032] Fig. 9 Shown are the high-resolution electron images and element distribution of PG-HOF prepared by the preparation method of the present invention.
[0033] Fig.10 Shown is the electron scanning image and element distribution (partial cross section) of PG-HOF / PES prepared by the preparation method of the present invention.
[0034] Fig.11 The figure shows the adsorption curve of perrhenate by PG-HOF / PES prepared by the preparation method of the present invention.
[0035] Fig.12 Shown is the adsorption isotherm of PG-HOF / PES prepared by the preparation method of the present invention for perrhenate ions of different concentrations.
[0036] Fig.13 Shown is the electron scanning image and element distribution (partial cross section) of PG-HOF / PES prepared by the preparation method of the present invention after adsorbing perrhenate.
[0037] Fig.14 The figure shows the removal effect of PG-HOF / PES prepared by the preparation method of the present invention on perrhenate under the coexistence of competing ions.
[0038] Fig.15 The figure shows the adsorption device of the present invention simulating the continuous operation state of the industrial water purification system.
[0039] Fig.16 It shows the continuous purification effect of PG-HOF / PES prepared by the preparation method of the present invention on simulated wastewater.
[0040] Fig.17 The figure shows the purification capacity of PG-HOF / PES prepared by the preparation method of the present invention after three cycles of regeneration. DETAILED DESCRIPTION
[0041] The present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0042] because 99 TcO4 – is radioactive, and ReO4 – The structure, charge density, size, etc. are almost the same, so they have extremely similar physical and chemical properties. Therefore, all experiments in this invention use ReO4 – As a substitute for nature research.
[0043] Example 1
[0044] Reference Figure 1 , a method for preparing an ionic liquid functionalized hydrogen bond organic porous framework composite resin, comprising the following steps:
[0045] Synthesis of hydrogen-bonded organic porous framework HOF: Weigh 10 mg of 1,3,6,8-tetrakis(benzoic acid)pyrene and dissolve it in 1 mL of N,N-dimethylformamide. Ultrasonicate the mixed solution until it becomes yellow and clear. Slowly add 0.5 mL of 1,2,4-trichlorobenzene. After heating at 80°C for 48 hours, yellow block crystals are obtained. After soaking in acetone solution for several times, dry it under vacuum conditions at 80°C for 12 hours to obtain HOF.
[0046] Synthesis of ionic liquid functionalized hydrogen bonded organic porous framework PG-HOF: Under N2 atmosphere, 1 equivalent of HOF and 4 equivalents of ionic liquid PG were fully mixed in 25-30 mL of methanol solution, wherein the ionic liquid PG was a copolymer of 1-vinyl-3-hydroxyimidazolium and bisvinylimidazolium, and 0.5 equivalent of 2,2'-azobis(isobutyronitrile)-methanol solution was injected into the mixed solution to initiate polymerization, and the mixture was heated to 65-80°C. After reacting for 24 hours, an equal amount of 2,2'-azobis(isobutyronitrile)-methanol solution was injected again, and the reaction was continued at 70°C for 24 hours. After cooling to room temperature, the yellow solid product was washed with a large amount of methanol and vacuum dried at 80°C for 12 hours to obtain PG-HOF.
[0047] Synthesis of composite resin beads PG-HOF / PES: 1.0 g polyethersulfone PES was dissolved in 1.0 mL N, N-dimethylformamide, fully stirred for 24 to 48 hours to obtain a transparent PES solution of uniform viscosity, 0.8 g of PG-HOF was added while hot, and the mixture was kept under continuous stirring overnight to allow PES and PG-HOF to form a uniform viscous mixture, the viscous mixture was transferred to a syringe and extruded through a needle, and the PG-HOF / PES solution was dropped into a precooled water / ethanol solution (volume ratio of 1:1) and immediately phase-inverted to form millimeter-scale composite resin beads PG-HOF / PES, and the composite resin beads PG-HOF / PES were allowed to stand in the water / ethanol solution, during which the solution was changed several times, and they were collected after 12 hours and vacuum dried at 80°C overnight to obtain dried composite resin beads PG-HOF / PES, hereinafter referred to as PG-HOF / PES, and the particle size of the prepared PG-HOF / PES was 2.00±0.1 mm.
[0048] Reference Figure 2 The structures shown in Figure a are the hydrogen-bonded organic porous framework HOF and the ionic liquid functionalized hydrogen-bonded organic porous framework PG-HOF; the design strategy shown in Figure b illustrates the hierarchical modification relationship among HOF, PG-HOF and PG-HOF / PES.
[0049] Comparative Example 1
[0050] Synthesis of covalent organic porous framework COF: Weigh 28.1 mg of 1,3,5-tris-(4-aminophenyl)benzene and 22.3 mg of 2,5-divinylterephthalaldehyde and dissolve them in 5 mL of acetonitrile. Ultrasonicate the mixture for 5 minutes to disperse the monomers evenly. Add 0.9 mL of 12 mol / L acetic acid (HAc) solution and shake vigorously for 1 minute. Let stand at room temperature for 3 days, collect the yellow precipitate by centrifugation at 8500 rpm, wash it three times with tetrahydrofuran and ethanol respectively, soak it in tetrahydrofuran for 48 hours, then centrifuge it again, and dry it under vacuum conditions at 120°C for 12 hours to obtain COF.
[0051] Synthesis of ionic liquid functionalized covalent organic porous framework PG-COF: Under N2 atmosphere, 1 equivalent of COF and 4 equivalents of ionic liquid PG were fully mixed in 25 mL of methanol solution, and 0.5 equivalents of 2,2'-azobis(isobutyronitrile)-methanol solution were injected to initiate polymerization, and the mixture was heated to 65-80°C. After reacting for 24 hours, an equal amount of 2,2'-azobis(isobutyronitrile)-methanol solution was injected again, and the reaction was continued at 65-80°C for 24 hours. After cooling to room temperature, the yellow solid product was washed with a large amount of methanol and vacuum dried at 80°C for 12 hours to obtain PG-COF.
[0052] Synthesis of composite resin beads PG-COF / PES: At 60°C, 1.0 g of polyethersulfone PES was dissolved in 1.0 mL of N,N-dimethylformamide and stirred for 24 to 48 hours to obtain a transparent PES solution of uniform viscosity. 0.8 g of PG-COF was added while hot, and the mixture was kept under continuous stirring overnight to allow PES and PG-COF to form a uniform viscous mixture. The viscous mixture was transferred to a syringe and extruded through a needle. The PG-MOF / PES solution was dropped into a precooled water / ethanol solution (volume ratio of 1:1) and immediately phase-inverted to form millimeter-scale composite resin beads PG-MOF / PES. The composite resin beads PG-MOF / PES were allowed to stand in the water / ethanol solution, during which the solution was changed several times. After 12 hours, they were collected and vacuum-dried at 80°C overnight to obtain dried composite resin beads PG-MOF / PES.
[0053] Comparative Example 2
[0054] Synthesis of metal organic porous framework MOF: Weigh 43.5 mg of chromium nitrate nonahydrate, 18.2 mg of terephthalic acid and 3 μL of 0.15 mmol / L hydrofluoric acid (HF) and disperse them in 0.5 mL of aqueous solution, transfer them to a hydrothermal autoclave and heat them continuously at 200 ° C for 8 hours. After cooling to room temperature, the synthesized green solid was heated to 70 ° C in water for 24 hours, heated to 60 ° C in ethanol for 3 hours, and heated to 80 ° C in N, N-dimethylformamide for 5 hours. After washing with dichloromethane several times, it was dried under vacuum at 160 ° C for 12 hours to obtain MOF.
[0055] Synthesis of ionic liquid functionalized metal organic porous framework PG-MOF: Under N2 atmosphere, 1MOF and 4 equivalents of ionic liquid PG were fully mixed in 25mL methanol solution, and 0.5 equivalents of 2,2'-azobis(isobutyronitrile)-methanol solution were injected to initiate polymerization, and the mixture was heated to 65-80°C. After 24 hours of reaction, an equal amount of 2,2'-azobis(isobutyronitrile)-methanol solution was injected again, and the reaction was continued at 65-80°C for 24 hours. After cooling to room temperature, the yellow solid product was washed with a large amount of methanol and vacuum dried at 80°C for 12 hours to obtain PG-MOF.
[0056] Synthesis of composite resin beads PG-MOF / PES: At 60°C, 1.0 g of polyethersulfone PES was dissolved in 1.0 mL of N,N-dimethylformamide and stirred for 24 to 48 hours to obtain a transparent PES solution of uniform viscosity, 0.8 g of PG-MOF was added while hot, and the mixture was kept under continuous stirring overnight to allow PES and PG-MOF to form a uniform viscous mixture, the viscous mixture was transferred to a syringe and extruded through a needle, and the PG-MOF / PES solution was dropped into a precooled water / ethanol solution (volume ratio of 1:1) and immediately phase-inverted to form millimeter-scale composite resin beads PG-MOF / PES, the composite resin beads PG-MOF / PES were allowed to stand in the water / ethanol solution, the solution was changed several times during the period, and the mixture was collected after 12 hours and vacuum-dried at 80°C overnight to obtain dried composite resin beads PG-MOF / PES.
[0057] The structural stability and special functional groups contained in PG-HOF / PES, PG-COF / PES and PG-MOF / PES obtained in Example 1 and Comparative Examples 1 and 2 were tested by X-ray diffraction and Fourier transform infrared spectroscopy.
[0058] Reference Figure 3 The X-ray diffraction patterns shown in (a), (b) and (c) respectively confirm that the corresponding crystalline skeletons in the obtained composite resins PG-HOF / PES, PG-COF / PES and PG-MOF / PES have high stability.
[0059] Reference Figure 4 The characteristic peaks of the imidazolium group (located at 1550-1560 cm-1) in the Fourier transform infrared spectra shown in (a), (b), and (c) –1 ) appeared in PG-HOF, PG-COF and PG-MOF, PG-HOF / PES, PG-COF / PES and PG-MOF / PES, respectively. The obvious S=O symmetric vibration in the polyethersulfone PES matrix was at 1241 cm –1 Appear.
[0060] The above characterization proves that during the continuous modification and compounding process of the technical solution of the present invention, the crystallinity of the organic porous framework is always retained.
[0061] Deep processing radionuclide experiments:
[0062] Trace adsorption experiments of PG-HOF, PG-COF and PG-MOF, PG-HOF / PES, PG-COF / PES and PG-MOF / PES were carried out at room temperature, and the initial concentration of Re in KReO4 solution (pH = 7) was 13 ppb. 10.0 mg of PG-HOF, PG-COF and PG-MOF, PG-HOF / PES, PG-COF / PES and PG-MOF / PES were added to 5.0 mL of KReO4 solution, respectively. Solution samples were collected after standing for 2 hours. After the initial solution and the solution after adsorption were diluted with 1% HNO3, the Re concentration in the solution was determined using an inductively coupled plasma mass spectrometer (ICP-MS). After the six groups of samples completed the adsorption, the remaining Re concentrations in the corresponding solutions were compared. Reference Figure 5 After treatment with PG-HOF and PG-HOF / PES, the residual concentration of Re element in the solution was only 0.059ppb (removal rate of 99.5%) and 0.038ppb (removal rate of 99.7%); after treatment with PG-MOF and PG-MOF / PES, the residual concentration of Re element in the solution was 0.371ppb (removal rate of 97.1%) and 0.248ppb (removal rate of 98.1%); after treatment with PG-COF and PG-COF / PES, the residual concentration of Re element in the solution was 0.912ppb (removal rate of 93.0%) and 0.403ppb (removal rate of 97.0%).
[0063] It is known that the World Health Organization (WHO) and the U.S. Environmental Protection Agency (EPA) have set 99 TcO4 – / ReO4 – The safety standards stipulated are 0.159ppb and 0.053ppb. The results of trace adsorption experiments show that the depth of removal of the composite resin is improved after granulation. This is due to the large number of pores evenly distributed in the polyethersulfone composite beads, which provide sufficient space for various crystalline porous materials functionalized with ionic liquids such as COF, MOF, and HOF. The relatively hydrophobic through-holes can promote mass transfer and transport, reduce the friction between water molecules and the side walls of the pores, and accelerate the ion exchange rate.
[0064] Under the confinement effect of the cavity, PG-HOF and PG-HOF / PES have a great influence on the performance of ReO4 – It shows obvious affinity advantage, which is because the hydroxyl fragments in the functional ionic liquid PG can undergo esterification reaction with the exposed carboxyl groups in the hydrogen-bonded organic framework HOF under mild conditions, and the polyionic liquid can effectively complex with HOF through covalent bonds to achieve precise functionalization and successfully enrich high-density ion exchange sites.
[0065] Considering that HOF materials generally have a large conjugated system, they can stabilize the free radicals generated by strong radiation and protect them from radiation damage; they have no metal atoms and comply with the CHON principle; they have high stability and self-healing properties under strong acidic conditions, and at the same time, they have not yet made in-depth developments in the safe disposal of radioactive anion nuclides. Therefore, the optimization of powdered HOF materials into composite resins will be of great significance to the field of strong acid spent fuel reprocessing.
[0066] Based on the above results, other qualitative characterizations of the materials described in the present invention were performed using HOF, PG-HOF, and PG-HOF / PES.
[0067] Test Example 1
[0068] X-ray photoelectron spectra of HOF, PG-HOF and PG-HOF / PES prepared in Example 1:
[0069] Reference Figure 6 The presence of N, Cl, and S element signals in the X-ray photoelectron spectroscopy corresponds to the functionalization and granulation process of the hydrogen-bonded organic framework.
[0070] Test Example 2
[0071] Thermal gravimetric experiments of HOF, PG-HOF, and PG-HOF / PES prepared in Example 1:
[0072] Reference Figure 7 The results of the thermogravimetric curves show that the hydrogen-bonded organic porous framework HOF has excellent thermal stability. With the introduction of the ionic liquid PG, the imidazolium group decomposes in the ionic liquid functionalized hydrogen-bonded organic porous framework PG-HOF at 300°C, while PG-HOF / PES has good skeleton stability due to its polyethersulfone matrix.
[0073] Test Example 3
[0074] High-resolution electron images and element distribution of HOF, PG-HOF, and PG-HOF / PES prepared in Example 1:
[0075] Reference Figure 8 The high-resolution electron images and element distribution of hydrogen-bonded organic porous frameworks (HOFs) confirmed that the selected HOFs were regular nanoparticles containing only C, H, and O elements.
[0076] Reference Fig. 9 The high-resolution electron image and element distribution results of the ionic liquid functionalized hydrogen-bonded organic framework PG-HOF show that the C element is evenly distributed in the entire PG-HOF, the O element is concentrated in the HOF area, and the N and Cl elements are concentrated in the polyimidazolium ionic liquid area. It can be seen that the HOF framework is densely wrapped by the polyionic liquid.
[0077] Reference Fig.10 ,The electron scanning images and element distribution images of PG-HOF / PES show that there are a large number of finger-like cavities inside the resin beads, the PG-HOF particles are evenly embedded in the PES matrix, the C and S signals cover the entire cross-sectional area, and the N and Cl elements correspond to PG-HOF.
[0078] Test Example 4
[0079] Adsorption kinetics experiment of PG-HOF / PES prepared in Example 1:
[0080] Reference Fig.11 At room temperature, the initial concentration of Re in the KReO4 solution (pH = 7) was 25 ppm. 10.0 mg PG-HOF / PES was added to 5.0 mL KReO4 solution. After standing for a certain period of time (0.5, 1, 2, 5, 10, 30 minutes), the solution samples were collected, and the initial solution and the adsorbed solution were diluted with 1% HNO3. The Re concentration in the solution was determined using an inductively coupled plasma mass spectrometer ICP-MS, and the removal rate was calculated. The removal rate of PG-HOF / PES in the first 30 seconds was as high as 98.92%, exceeding 99.88% of ReO4 – It was successfully removed within 10 minutes.
[0081] Test Example 5
[0082] Adsorption isotherm experiment of PG-HOF / PES prepared in Example 1:
[0083] Reference Fig.12 At room temperature, the initial concentration of Re in KReO4 solution (pH = 7) ranged from 50 to 800 ppm. 10.0 mg of ionic liquid functionalized hydrogen bonded organic framework porous composite resin beads PG-HOF / PES were added to 5.0 mL of KReO4 solution with different initial concentrations. After standing for 12 hours, the solution samples were collected. After the initial solution and the adsorbed solution were diluted with 1% HNO3, the Re concentration in the solution was determined by inductively coupled plasma mass spectrometry ICP-MS, and the removal rate was calculated. Effect of PG-HOF / PES on ReO4 – The maximum adsorption capacity is 976.9 mg g –1 .
[0084] Reference Fig.13 , Electron scanning image and element distribution of PG-HOF / PES after adsorption of perrhenate. The S element appears along the boundary of the polyethersulfone polymer matrix, while the Re element corresponds to the distribution trend of PG-HOF particles embedded in the matrix.
[0085] Test Example 6
[0086] Selective adsorption experiment of competitive ions on PG-HOF / PES prepared in Example 1:
[0087] Reference Fig.14 At room temperature, 0.5 mM NaNO3, NaNO2, Na2SO4, NaClO4, K3PO4 and Na2CO3 solutions were mixed with 0.5 mM KReO4 solution to prepare a KReO4 solution containing a single competitive ion (molar ratio of 1). 10.0 mg PG-HOF / PES was added to 5.0 mL of the mixed solution. After standing for 12 hours, the solution samples were collected. The initial solution and the adsorbed solution were diluted with 1% HNO3, and the Re concentration in the solution was determined by inductively coupled plasma mass spectrometry ICP-MS. The removal rate was calculated. PG-HOF / PES can still accurately capture more than 98.63% of ReO4 under the interference of coexisting competitive anions. – PG-HOF / PES of Example 1 of the present invention has a great influence on ReO4 – ( 99 TcO4 – It has a certain affinity, which is reflected in extremely fast kinetics, excellent adsorption capacity and accurate selectivity.
[0088] Reference Fig.15 , shown is an adsorption device of the present invention simulating the continuous operation state of an industrial water purification system. The left side of the figure shows a schematic diagram of the adsorption device, and the right side shows a digital photo of the continuous dynamic adsorption device.
[0089] Test Example 7
[0090] Dynamic continuous adsorption experiment of PG-HOF / PES prepared in Example 1:
[0091] The low-concentration wastewater to be purified (containing 12.298 ppb Re) was pumped by a peristaltic pump at a fixed flow rate of 1.0 mL min -1 The sample was transferred to a composite resin bead adsorption column (1.0 g PG-HOF / PES and a small amount of quartz sand were filled in each adsorption column). The effluent was collected at regular intervals at the outlet of the second adsorption column. After the sample was diluted with 1% HNO3, the Re concentration in the effluent was determined by inductively coupled plasma mass spectrometry (ICP-MS). The deep purification ability of PG-HOF / PES was analyzed by reference. Fig.16 , 1.0 g PG-HOF / PES can effectively purify 1200.0 mL of wastewater, and the Re concentration can be reduced to 0.049 ppb.
[0092] Test Example 8
[0093] Sustainability exploration experiment of PG-HOF / PES prepared in Example 1:
[0094] 3 mol / L hydrochloric acid solution was used as the eluent at a rate of 2.0 mL min -1 The entire adsorption device was flushed at a fixed flow rate. After the PG-HOF / PES was dried at room temperature, it was ready for the next round of dynamic adsorption experiments. Fig.17 PG-HOF / PES can be reused continuously for at least three cycles, that is, 1.0 g of PG-HOF / PES of the present invention can deeply purify 4.8 L of low-concentration wastewater.
[0095] By adjusting the process parameters according to the content of the present invention, the PG-HOF / PES of the present invention can be prepared, and the performance is basically the same as that of Example 1.
[0096] The above is only a preferred embodiment of the present invention. It should be pointed out that, for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing ionic liquid functionalized hydrogen bonded organic porous framework composite resin beads, characterized in that: The following steps are involved: Step 1, synthesizing an ionic liquid functionalized hydrogen-bonded organic porous framework IL-HOF using an ionic liquid IL and a hydrogen-bonded organic porous framework HOF, wherein the ionic liquid is copolymerized by the same or different monomers containing alkenyl groups, at least one of the monomers includes an imidazolium group, and at least one of the monomers includes an amino group or a hydroxyl group, and the amino group or the hydroxyl group reacts with a naked carboxyl group in the HOF by esterification or amide reaction; Step 2, compounding the IL-HOF obtained in step 1 with PES to form an ionic liquid functionalized hydrogen bonded organic porous composite resin IL-HOF / PES dispersion; Step 3, dropping the IL-HOF / PES dispersion obtained in step 2 into a pre-cooled water / ethanol solution to cause phase inversion, and then standing and drying to obtain composite resin beads IL-HOF / PES.
2. The method for preparing the ionic liquid functionalized hydrogen bonded organic porous framework composite resin beads according to claim 1, characterized in that: The ionic liquid IL is a copolymer of 1-vinyl-3-aminoimidazolium, a copolymer of 1-vinyl-3-hydroxyimidazolium, or a copolymer of bisvinylimidazolium and an olefin-containing alcohol or ammonia.
3. The method for preparing the ionic liquid functionalized hydrogen bonded organic porous framework composite resin beads according to claim 1, characterized in that: The particle size of the composite resin beads IL-HOF / PES is 2.00±0.1 mm.
4. The method for preparing the ionic liquid functionalized hydrogen bonded organic porous framework composite resin beads according to claim 1, characterized in that: Step 1 is specifically as follows: under a protective gas atmosphere, the hydrogen-bonded organic porous framework HOF and the ionic liquid IL are fully mixed, an initiator solution is injected to initiate polymerization, heating is performed, an equal amount of initiator solution is injected again, and the reaction is heated again to obtain a solid product. After cooling, the obtained solid product is washed, and the ionic liquid functionalized hydrogen-bonded organic porous framework IL-HOF is obtained after heating and drying.
5. The method for preparing the ionic liquid functionalized hydrogen bonded organic porous framework composite resin beads according to claim 1, characterized in that: Step 2 is specifically as follows: under heating conditions, PES is dissolved and fully stirred to obtain a transparent PES solution of uniform viscosity, and the ionic liquid functionalized hydrogen bond organic porous framework IL-HOF prepared in step 1 is added while hot, and continuous stirring is performed to allow PES and IL-HOF to form a uniform IL-HOF / PES dispersion.
6. The method for preparing the ionic liquid functionalized hydrogen bonded organic porous framework composite resin beads according to claim 4, characterized in that: The mass ratio of the hydrogen-bonded organic porous framework HOF, the ionic liquid IL and the initiator in step 1 is (0.8-1.5):(3.2-6.0):(0.4-0.6), and the initiator solution is a methanol solution of 2,2'-azobis(isobutyronitrile).
7. The method for preparing the ionic liquid functionalized hydrogen bonded organic porous framework composite resin beads according to claim 1, characterized in that: In step 1, the reaction temperature is 65-80° C., the reaction time is 24-36 hours, and the washing solution is one of methanol or N,N-dimethylformamide.
8. The method for preparing the ionic liquid functionalized hydrogen bonded organic porous framework composite resin beads according to claim 5, characterized in that: In step 2, the mass ratio of PES to IL-HOF is 1.25:1, the reaction temperature is 60° C. to 80° C., and the reaction time is 24 to 48 hours.
9. Composite resin beads IL-HOF / PES prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the composite resin beads IL-HOF / PES according to claim 9 in deep treatment of radionuclides.